Facile preparation of humidity stable green γ‐cyclodextrin metal–organic framework monolith for CO2 capture - Fan, Shu‐Ting; Chen, Zhi‐Hui; Yang, Zhang; Feng, Jun‐Feng; Yu, Lu‐Ping; Qiu, Zhen‐Jiang; Liu, Wen‐Tao; Li, Bang‐Jing; Zhang, Sheng (AIChE journal, 2022)
Processing powdered metal–organic frameworks (MOFs) into more usable forms can greatly expand their practical applications. We report a very simple and efficient method for synthesizing a green‐friendly γ‐cyclodextrin (CD)‐MOF monolith (rather than powder), without using any connectors or high temperature/pressure. Compared with the γ‐CD‐MOF‐powder, the γ‐CD‐MOF‐monolith showed much better humidity stability because the MOF particles in the γ‐CD‐MOF‐monolith were tightly packed. In addition, the CO2 adsorption test indicated that it had a higher volume adsorption capacity for CO2, with adsorption capacities of 44.04 and 36.85 cm3/cm3 at 0 and 25°C, respectively. The γ‐CD‐MOF‐monolith can maintain its porous structure and gas adsorption capacity even after 14 days of exposure to humid conditions, and the amount of CO2 absorption remains almost unchanged. This humidity stable γ‐CD‐MOF‐monolith is expected to have greater practical applications than its powdered counterpart in many applications including CO2 adsorption.